2019
DOI: 10.33846/sf.v10i3.488
|View full text |Cite
|
Sign up to set email alerts
|

Persepsi Keparahan Kanker Serviks dan Keteraturan Melakukan Deteksi Dini Kanker Serviks

Abstract: Cervical cancer is currently a global health problem. One of cervical cancer prevention is perform early detection. The purpose of this study was to analyze the relationship between women’s perceived severity of cervical cancer and the regularity of early detection of cervical cancer. The research design was cross sectional. The research subject were women aged 30-50 years in working area of the Kalisat community health center in Jember Regency East Java as much as 92 womens with inclusion criteria was women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The fact that happened is the number of early detection coverage of cervical cancer nationally in 2017 reached 2.98%. This number has not yet reached the determined national target (9,10).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The fact that happened is the number of early detection coverage of cervical cancer nationally in 2017 reached 2.98%. This number has not yet reached the determined national target (9,10).…”
Section: Introductionmentioning
confidence: 95%
“…Similar study also reported that knowledge, attitude and perception related to HPV vaccination and infection were lacking among female in Lagos, Nigeria (18). However, Roger argues on a theory of cognitive behavior, protection motivation theory, a person's attitude can be influenced by the threat of judgment, one of which is the perception of the severity of an illness (9). Attitude of cervical cancer, HPV and HPV vaccination will arise due to the perception of the severity of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%